The Complexities of Colorectal Cancer: A Case Report - Intan Fredika Bahari; Arifin, Mohamad (HM Publisher, 2024)
Background: Colorectal cancer (CRC) is a malignancy that originates from the colon tissue (ascending, transverse, descending, sigmoid colon) and rectal tissue. Colorectal cancer is the fourth most common cancer in the world, and the second leading cause of cancer death. In Indonesia (2020), colorectal cancer was ranked sixth of the all malignancy diagnoses with a total of 17,368 new cases (4,4%). Case presentation: a case of colon cancer (mucinous adenocarcinoma) in a 70 year old woman. Diagnosis was based on anamnesis of the presence onf intermitten abdominal pain, a mass in the right iliac region of the abdomen, and defecation accompanied by blood. On physical examination, there was tenderness and a mass in the right iliac region, and a positive Carnett’s sign. computer tomography (CT) of the urinary tract without contrast was performed and revealed a mass was found in the right abdomen, suspicious for the ascending colon and hepatic flexure of the colon, a cyst with a diameter of ± 3cm in the right kidney. Conclusion: Anatomical patology (microscopic) results showed mucinous adenocarcinoma. The treatment for this patient was exploratory laparotomy, right hemicolectomy, and end to end anastomosis.